Pharmacogenetic Testing: Effectiveness of the Use of the Indirect Anticoagulant Warfarin - Oxana Bogaevskaya (Journal of Global Pharma Technology, 2020)
There are some particularities of managing patients who have been taking anticoagulants for a long time and who need dental treatment. People who regularly receive oral anticoagulant therapy are at increased risk of bleeding during and after surgery in the oral cavity. Clinicians must constantly weigh the risk of postoperative bleeding with continued therapy, as well as the risk of thromboembolic complications when the drug is discontinued. The purpose of this study is to study the effectiveness and safety of the indirect anticoagulant Warfarin in patients with diseases of the cardiovascular system undergoing dental treatment. In 2017-2018, based on the Moscow dental clinic No. 2 (Russian Federation), studies were conducted in which 350 patients participated, of which 5 were excluded from the sample. Moscow cardiological dispensary No. 1 patients who applied for dental care were involved. The first group consisted of 30 people with a diagnosis of severe diseases of the cardiovascular system (coronary heart disease, etc.), the second - 65 people with an average risk of thrombosis, the remaining 250 people of the 3rd group are patients with a low risk of thrombosis. Instead of Warfarin, the first two groups received low molecular weight heparin, the third - continued the course of Warfarin. In addition to general clinical methods (ECG, maintaining the INR level (international normalized ratio), etc.), examinations used a selection of local anesthetics and vasoconstrictors. Significant differences in the INR level before and after the operation between the three groups were not found - all of them were within normal limits. The maximum number of bleeding cases in patients from the 1st group is 2.1 times higher than in the 2nd group (p ≤ 0.01), and 3.5 times higher than in the first (p ≤ 0.001). Between the 2nd and 3rd group the difference was 1.6 times (p ≤ 0.05). Regardless of the use or rejection of Warfarin, the maximum number of bleeding cases during dental procedures occurs in patients with severe cardiovascular diseases. Refusal from Warfarin is justified in case of severe diseases of the cardiovascular system, but in the case of a low level of thrombosis, therapy with Warfarin is possible. The risk of bleeding is evenly distributed within each group, regardless of the combined use of a vasoconstrictor and anesthetic or only anesthetic, while maintaining the difference between the groups. We have shown that the severity of diseases of the cardiovascular system can also influence the number of cases of bleeding during dental interventions. The complexity of the dental intervention determines the likelihood of bleeding. In the first group, for patients who had one tooth removed, bleeding was observed 5 times less compared with removal of the cyst (p ≤ 0.001), and 4 times less - compared with operations on the pulp (p ≤ 0.001). Pearson's correlation between the type of dental intervention and the number of bleeding in this group is the highest (0.91), 0.82 in the 2nd group, 0.56 in the 3rd. The type of dental intervention, regardless of the use of Warfarin, has a direct relationship with the number of bleeding. The maximum number of bleeding is observed in patients with severe pathologies of the cardiovascular system.Keywords: Effectiveness and safety of dental treatment, Warfarin, INR, Anticoagulants, Anesthetics, vasoconstrictors, Injection pain relief, Pharmacogenetic testing.